2007
DOI: 10.1111/j.1365-2257.2006.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis‐induced immune thrombocytopenia mimicking ITP: a report of seven cases

Abstract: Brucellosis continues to be an important cause of fever in underdeveloped countries and in rural areas of developed world. It is a multisystemic disease, associated with wide variety of symptoms. A wide variety of symptoms, including haematological abnormalities, such as anaemia, thrombocytopenia, pancytopenia, dissemine intravascular coagulation and leucopoenia could be seen, all of which are more common than usually thought. In this short study, we present a relatively uncommon haematological manifestation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…On the other hand, brucellosis is a multisystem disease with a broad spectrum of clinical manifestations; hematological abnormalities ranging from fulminant disseminated intravascular coagulation to anemia, leucopoenia, thrombocytopenia, and clotting disorders can occur [11,12]. Disseminated intravascular coagulation (DIC) is common in patients with bacterial septicemia; however, it is rare in patients with brucellosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, brucellosis is a multisystem disease with a broad spectrum of clinical manifestations; hematological abnormalities ranging from fulminant disseminated intravascular coagulation to anemia, leucopoenia, thrombocytopenia, and clotting disorders can occur [11,12]. Disseminated intravascular coagulation (DIC) is common in patients with bacterial septicemia; however, it is rare in patients with brucellosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated intravascular coagulation (DIC) is common in patients with bacterial septicemia; however, it is rare in patients with brucellosis [11,12]. Bacterial products such as endotoxin can cause endothelial damage or bind to platelets, causing them to aggregate and be removed from the circulation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Brucella-associated thrombocytopenia can be associated with hypersplenism, autoimmune destruction due to the development of antithrombocyte antibodies, disseminated intravascular coagulopathy (DIC), hemophagocytosis and granulomas in bone marrow (6,9,11,13,14). Sevinc et al (12) presented the case of a patient who presented with thrombocytopenia of 9,000/mL and received a diagnosis of transient ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported good responses to steroid treatment in patients with thrombocytopenia induced by Brucella spp. Plasma exchange, intravenous gamma globulin administration or antibacterial treatment only have also been used successfully in some patients (6,11,12,14,16). We found no brucellosis cases of steroid-refractory thrombocytopenia reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation